Polyhydroxyalkanoates as biomaterials. Issue 9 (28th July 2017) - Thorat Gadgil, Bhagyashri S.; Killi, Naresh; Rathna, Gundloori V. N.
Abstract : Polyhydroxyalkanoates are being explored exponentially for biomedical application. The collative reported information on polyhydroxyalkanoates may serve as a guide to attain novel biomaterials. Abstract : Polyhydroxyalkanoates (PHAs) are biopolymers synthesized by bacteria under unbalanced growth conditions. These biopolymers are considered as potential biomaterials for future applications because they are biocompatible, biodegradable, and easy to produce and functionalize with strong mechanical strength. Currently, PHAs are being extensively innovated for biomedical applications due to their prerequisite properties. The wide range of biomedical applications includes drug delivery systems, implants, tissue engineering, scaffolds, artificial organ constructs, etc. In this article we review the utility of PHAs in various forms (bulk/nano) for biomedical applications so as to bring about the future vision for PHAs as biomaterials for the advancement of research and technology.